Compression of multi channel audio at low bit rates using the AMR-WB+ codec - Abrahamsson, Lars (2005)
The purpose of this thesis work done at Ericsson Research in Luleå was to investigate the possibilities of encoding 5.1 surround sound for low bit rates using the AMR-WB+ audio encoding technique. In the first phase of the work, investigations of the inter-channel dependencies were carried out, and the main tool used was Matlab. Several efforts were made aiming to reduce the total energy of the signal. This was done by decorrelating the sound channels using ordinary linear predictors. Decorrelation attempts were performed in the time domain as well as in the frequency domain. After decorrelating the channels, each channel was encoded in an individual bit rate using the mono mode of AMR-WB+ with bit rates proportional to the relative energy content. However, listening tests combined with studies of the energy reduction achieved by decorrelations indicated that, for a given bit rate, there is in general no advantage decorrelating the signal compared to not doing so. The second phase of the thesis work mainly consisted of modifying the existent C code of the AMR-WB+ mono coder in order to suit it for 5.1 sound encoding and decoding. The goal was "the simplest possible", an encoder that encoded each unmodified sound channel individually, distributing the bit rates over the channels aiming to keep the sums of the bit rates over the channels approximately constant over time. Opposed to the five "normal" sound channels, the encoding of the LFE (Low Frequency Element) was done in a specific way making use of this, compared to the other channels, somewhat constrained signal. Furthermore, the method of encoding high frequency sounds of AMR-WB+, the BWE (BandWidth Extension), needed to be modified at some extent. Finally, the third phase consisted mainly of evaluation of the product made and of making comparisons to competing low bit rate multi channel coders. Validerat; 20101217 (root)